Toward Interfaith Ecological Ethics: Synergizing Religious Eco- Theology and Local Cultural Wisdom for Environmental Governance in Indonesia - Arwansyah Bin Kirin; Zul Kariman (MD Research Center, 2026)
Environmental degradation represents not only a physical crisis but also a profound spiritual and ethical disconnect between humanity and nature. This study aims to analyze the synergy between eco-theology and local cultural wisdom in constructing a contextual interfaith ecological ethics framework in Indonesia. Using a qualitative literature-based approach, this research examines eco-theological constructions within Islam, Christianity, Hinduism, Buddhism, and Indigenous Beliefs, alongside manifestations of local wisdom in conservation practices such as Subak, Sasi, and Leuweung Larangan. The findings reveal that integrating spiritual principles with cultural practices enriches the moral dimension of environmental conservation and significantly enhances community participation. The study concludes that the ecological crisis is fundamentally a crisis of values, requiring a holistic approach that integrates theological insights with cultural practice. The resulting “Interfaith Ecological Ethics” framework offers a transformative pathway for sustainable development in Indonesia, rooted in society’s spiritual and cultural values, while challenging dominant secular-anthropocentric environmental paradigms.